Symmetry Reduction Method for Exact Solutions of Some Nonlinear Systems - Kaur, Bikaramjeet (My University, 2010)
The Thesis entitled “SYMMETRY REDUCTION METHOD FOR EXACT SOLUTIONS OF SOME NONLINEAR SYSTEMS” is attempted to find some exact solutions of nonlinear systems of partial differential equations (PDEs) governing some important physical phenomenons by using Symmetry reduction method which is based on Fréchet derivatives of the differential operators and we drive Lie algebra which then helps us to obtain the optimal system of generators. Then, we find reduced ordinary differential equations (ODEs) from given nonlinear PDEs equations and some exact solutions of them.
Keywords: Symmetry Reduction Method; Exact Solutions